Good faith as legal parameter to identify the type emptio spei or rei emptio speratae in the contract of sale of future thing - Hurtado Palomino, José Vicente; Universidad Santo Tomás Bucaramanga (Universidad Santo Tomás Seccional Bucaramanga, 2015)
From a sociological angle, the buying and selling contract of future products has been consolidated in the agrobusiness field, as long as it facilitates a series of benefits from a financial, technical, or simply a convenience point of view for those who intent to use it with the purpose of commercialize or to buy future produce. From a legal point of view, the contract type previously mentioned is recognized in the Colombian law and it is classified according to the level of uncertainty of the future existence of the produce, which at the moment when the contract takes place it is nonexistent but there is a high probability of its existence in the future. The first classification is of aleatory nature and the second one is of commutative nature. Nevertheless, the laws that regulate them do not establish a clear solution in the event that the parties do not specify the type of buying and selling contract that took place in the negotiation. In order to solve the issue previously discussed, the present document suggests as a parameter to identify the type of buying and selling contract of future product the principle of good faith.